Pparγ Expression in T Cells as a Prognostic Marker of Sepsis. Issue 6 (June 2016) - Brenneis, Marco; Aghajaanpour, Ramin; Knape, Tilo; Sha, Lisa K.; Neb, Holger; Meybohm, Patrick; Zacharowski, Kai; Hauser, Ingeborg A.; Büttner, Stefan; Parnham, Michael J.; Brüne, Bernhard; von Knethen, Andreas
Abstract : ABSTRACT: Translating murine data to the human situation, we proposed that the level of peroxisome proliferator-activated receptor γ (PPARγ) expression in T cells from septic patients correlates with clinical outcome. In this preliminary report, we analyzed PPARγ mRNA expression in CD3 + T cells derived from blood of a very small number of septic patients (n = 18) on various days up to 2 weeks after the initial diagnosis. CD3 + T cell count was determined by flow cytometry. T cells from n = 11 healthy donors were included as controls. Maximal PPARγ mRNA expression was observed on the day of sepsis diagnosis (day 0; 5, 896 ± 1, 523 copies PPARγ mRNA/25 ng mRNA, * P < 0.05 vs. controls). In contrast, the number of CD3 + T cells was significantly decreased in septic patients compared with healthy controls (296 ± 31 vs. 1, 803 ± 134 T cells/μL blood, *** P < 0.001). Setting two arbitrary limits: patients with a PPARγ expression in T cells higher than 7, 000 copies/25 ng mRNA, of whom five of six patients died during the ICU stay, and patients with a T cell count below 100 T cells/μL blood, of whom five of eight patients died, we identified a correlation between sepsis survival and low T cell number, paired with high T cell-specific PPARγ expression. Among all 18 sepsis patients, four fulfilled the criteria for both arbitrary settings and all four of these patients subsequently died. We suggest that both high PPARγ expression in T cells and low absolute T cell number in blood of septic patients may have the potential as a new prognostic marker for a poor sepsis outcome. Abstract : Supplemental Digital Content is available in the text